2004
DOI: 10.1109/lpt.2004.834919
|View full text |Cite
|
Sign up to set email alerts
|

High Absorption and Low Splice Loss Properties of Hexagonal Double-Clad Fiber

Abstract: Abstract-An accurate experimental comparison of the pump absorption and the lasing features between Nd 3+ -doped fiber lasers using hexagonal-shaped and D-shaped fiber is reported. The measured slope efficiencies with respect to the absorbed pump power of 805 nm are nearly identical at 65.3% for both fibers. Taking advantage of the near symmetrical shape of the hexagonal fiber, the lowest reported splice loss of 0.05 dB is achieved between the double-clad fiber and standard 125-m fiber with the use of the fibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…For the monolithic amplifier tested in this work residual pump data showed that some fraction of the pump did not interact with the core. To increase pump scrambling a kidney coil [8] was tried, which did not result in a significant effect. Other pump scrambling methods were not implemented but could possibly have been used to increase the efficiency of the amplifier.…”
Section: Monolithic Amplifiermentioning
confidence: 99%
“…For the monolithic amplifier tested in this work residual pump data showed that some fraction of the pump did not interact with the core. To increase pump scrambling a kidney coil [8] was tried, which did not result in a significant effect. Other pump scrambling methods were not implemented but could possibly have been used to increase the efficiency of the amplifier.…”
Section: Monolithic Amplifiermentioning
confidence: 99%
“…Standard, bend-sensitive glass fibres subjected to 2-5 mm radii of bending and power levels of 1-2 W in the near-infrared wavelength window can fail in a few minutes [11]. Therefore, double-clad fibres [12,13] or multi-core fibres [7] are used, which are not employed as typical optical fibres in FTTX networks.…”
Section: Study Of Power-over-fiber Technologymentioning
confidence: 99%
“…Avoiding the formation of the spiral light, the circular symmetry structure of inner cladding was broken. Considering the splicing, [12] the octagonal structure was proved to be the most reasonable, which can ensure that 99% pump power was absorbed by the core. Figure 2(b) shows that there are two layers of coating around the inner cladding, which are called the outer cladding and the protective coating.…”
mentioning
confidence: 99%